Self-reported social support at works among nurses and associated factors. Results from a cross-sectional study in a provincial hospital in 2020. - Tran Thi Thu, Thuy; Nguyen Thi, Huong; Nguyen Van, Bang; Le Thi Thanh, Xuan (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objective: This study aimed to measure nurses' self-perceived social support and identify associated factors at one Vietnamese provincial hospital in 2020. Methods: A cross-sectional study was implemented among clinical nurses of 22 treatment wards working at the hospital for over six months. Two hundred sixty-one nurses returned the self-reported questionnaires containing the Vietnamese 22-item Job Content Questionnaire and set of questions on personal and work characteristics. Descriptive analysis (frequency, mean, standard deviation), crude analysis (t-test and ANOVA), and multivariate linear regressions were conducted to describe the social support (i.e., supervisor' and co-worker's supports) and their associations with other factors at the significant level p less than 0.05. Results: The study achieved a relatively high response rate (82.1%). Social supports, including supervisor and co-worker's supports, were 24.04, 11.89, and 12.16, respectively. Multivariate Linear regressions showed an inverse association of job demand and positive correlation of job control with both supervisor and co-workers' support among participating nurses (p<0.01). Older nurses, nurses with fewer years of work experience or fixed-term contract reported more perceived support from their superiors (p<0.05). Conclusions: Nurses with different characteristics reported dissimilar perceived levels of social supports at work. Head nurses responsible for nursing management should encourage a supportive working environment where nurses can feel comfortable asking for and receive assistance from others. In addition, appropriate training would be helpful to increase nurses' recognition and usage of available resources at work.